Connectivity of digital marketing communication strategy between tourism facilities and interests - Syaiful Rohim (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
Tourism facilities contribute significantly to enhancing the tourist experience by offering comfort, cleanliness, safety, and entertainment. However, their direct effect on tourism interest remains unclear. This study examines the relationship between tourism facilities, digital marketing communication strategies, and tourism interest using a mediated model. A quantitative survey was conducted on Pari Island, Seribu Islands, involving 223 tourists selected through purposive sampling. Respondents were aged 17 or older and had visited within the past six months. Path analysis was used to analyze the data. Results show no significant direct effect between facilities and tourism interest. However, digital marketing strategies strongly mediate the relationship. These strategies promote tourism facilities and engage tourists through interactive communication. The study highlights the importance of digital platforms in shaping tourism interest. Future research is recommended to explore this model across destinations, timeframes, and demographic segments using Structural Equation Modeling (SEM) for broader insights.